Short- and long-term ex post evaluation of community based environmental initiatives in Chile - Cristian Mardones (CEPAL Review, 2019)
This study contributes to the limited literature on environmental impact assessments by undertaking an ex post evaluation of a programme to improve the environment through various community-based initiatives that promote education and citizen participation in Chile. In line with the selection criteria for the projects and the nature of the data available, the instrumental variables method is used to determine this programme's effect on perceived problems associated with multiple environmental issues. The results reveal that, in the short term, only the perception of odour pollution improves, while, in the long term, the impact on that issue increases twofold and the perception of air pollution and pollution caused by stray dogs both improve by a similar magnitude.